A case of ovarian mesothelioma with VHL mutation diagnosed by immunohistochemistry and literature review - Yao, Ye; Yan, Hao; Xiong, Jing; Duan, Yaqi (Frontiers in Oncology, 2024)
The malignant mesothelioma mainly develops in the pleura and peritoneum, while primary ovarian mesothelioma is very rare. Here, we report the first case of primary ovarian mesothelioma (clear cell variant) with VHL mutations in the world based on the results of histomorphology, immunohistochemistry, and genetic testing. This is an extremely rare type of tumor that has not been reported so far. Through the literature search, we reviewed primary ovarian mesothelioma, focusing on its differential diagnosis and molecular genetics. The purpose of this paper is to deepen the flexible selection and application of immunohistochemical markers in mesothelioma, so as to reduce missed diagnosis and misdiagnosis.